The tradition of pilgrimage to the grave of Muslim missionaries in Misool Island, Papua - Ade Yamin,; Mufliha Wijayati,; Ana Maria Fatimah Parera,; Rahmawansyah Sahib, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The aim of this article is to reveal the meaning behind the grave considered sacred by the community. This paper attempts to explain the relationship between the pilgrimage tradition at the sacred grave and the fulfilment of the necessities of life, as well as the strong influence of traditional and religious values in determining the standards of values and norms prevailing in community on Misool Island, Raja Ampat. Through ethnographic works by tracing the existence of old grave on Misool Island, Raja Ampat, and by carefully listening to the explanations of community leaders verbally describing the history of the tomb, there are enough reasons to explain the close relationship between the values believed and practiced in the life of Misool society and the sacredness of some existing graves. This study explains the importance of the position of grave in connecting people’s hope to the noblest Essence. The symbolizing of the grave as something extraordinary in this society also turns out to be a way to maintain the continuity of people’s hope with the reality that many cultural and structural obstacles are encountered.